1996
DOI: 10.1099/00207713-46-1-234
|View full text |Cite
|
Sign up to set email alerts
|

Agrococcus jenensis gen. nov., sp. nov., a New Genus of Actinomycetes with Diaminobutyric Acid in the Cell Wall

Abstract: Actinomycetes are considered an inexhaustible source of chemically diverse secondary metabolites. In addition to the genera Streptomyces, Micromonospora, and Actinoplanes, coryneform and nocardioform bacteria have been used in screening programs for new compounds of medical and biotechnological importance (5, 8).In the course of a program aimed at isolating actinomycetes that have potential for producing novel bioactive compounds, we isolated a large number of strains from different soils. In about 65 of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
487
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 551 publications
(501 citation statements)
references
References 17 publications
12
487
2
Order By: Relevance
“…Diaminopimelic acid [11] and the composition of cell-wall sugars [12] was identified by TLC of the whole-organism hydrolysate. Fatty acids were determined by GC-MS [13,14], and menaquinones by reversed-phase HPLC [15,16]. 16S rRNA gene amplification and determination of the almost complete sequence (1495 bp) were carried out according to Rainey et al (1996) [17].…”
Section: Taxonomy Of the Producing Strain Tü 6368mentioning
confidence: 99%
“…Diaminopimelic acid [11] and the composition of cell-wall sugars [12] was identified by TLC of the whole-organism hydrolysate. Fatty acids were determined by GC-MS [13,14], and menaquinones by reversed-phase HPLC [15,16]. 16S rRNA gene amplification and determination of the almost complete sequence (1495 bp) were carried out according to Rainey et al (1996) [17].…”
Section: Taxonomy Of the Producing Strain Tü 6368mentioning
confidence: 99%
“…Menaquinones were extracted as described by Collins et al (1977) and analysed by HPLC (Groth et al, 1996). The isolate contained dihydrogenated menaquinones with eight isoprene units [MK-8(H 2 )] as the major isoprenologue and minor amounts of MK-6(H 2 ) and MK-7(H 2 ).…”
mentioning
confidence: 99%
“…2). Determination of the isomers of diaminopimelic acid and sugars in whole-organism hydrolysates were performed as described by Groth et al (1996). Detection of mycolic acids was performed according to the method of Minnikin et al (1975) with some modifications by thin layer chromatography of their methanolic esters.…”
mentioning
confidence: 99%
“…Polar lipids were extracted according to the method of Minnikin et al (1979), and were identified by two-dimensional TLC and spraying with specific reagents (Collins & Jones, 1980). Menaquinones were analysed by HPLC as described by Groth et al (1996), and the menaquinones of V. marismortui DSM 12325 T and V. halodenitrificans DSM 10037 T were analysed in parallel with those of strain YIM kkny16 T under identical conditions. Cells were prepared as described by Lee et al (2006) and An et al (2007), and cellular fatty acid methyl esters were identified according to the standard protocol of the Microbial Identification system (MIDI; Microbial ID).…”
mentioning
confidence: 99%